Stability of the Nine Sky Quality Meters in the Dutch Night Sky Brightness Monitoring Network - Peter den Outer; Dorien Lolkema; Marty Haaima; Rene van der Hoff; Henk Spoelstra; Wim Schmidt (Sensors, 2015)
In the context of monitoring abundance of artificial light at night, the year-to-year stability of Sky Quality Meters (SQMs) is investigated by analysing intercalibrations derived from two measurement campaigns that were held in 2011 and 2012. An intercalibration comprises a light sensitivity factor and an offset for each SQM. The campaigns were concerned with monitoring measurements, each lasting one month. Nine SQMs, together forming the Night Sky Brightness Monitoring network (MHN) in The Netherlands, were involved in both campaigns. The stability of the intercalibration of these instruments leads to a year-to-year uncertainty (standard deviation) of 5% in the measured median luminance occurring at the MHN monitoring locations. For the 10-percentiles and 90-percentiles, we find 8% and 4%, respectively. This means that, for urban and industrial areas, changes in the sky brightness larger than 5% become detectable. Rural and nature areas require an 8%–9% change of the median luminance to be detectable. The light sensitivety agrees within 8% for the whole group of SQMs.